PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 005 RAJA BEJAMU KECAMATAN SINABOI - Zulkifli '; Syahrilfuddin '; Zariul Antosa Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Problem background of this research that student do not understand about Math lesson. It is shown that only few of students that ask the teacher and answer the questions. The average score result of Math test is still low, that is 58,4. And only 7 of 25 student or 28% in class can reach standard of KKM, while score of KKM is 65. This is the problem: “Do the Cooperative Learning Model type Two Stay Two Stray (TSTS) improve Math studying result, Students of class IV SDN 005 Raja Bejamu Kecamatan Sanaboi Kabupaten Rokan Hilir?”. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: “If the Cooperative Learning Model type Two Stay Two Stray (TSTS) is applied therefore gets to increase Math studying results, Student of class IV SDN 005 Raja Bejamu Kecamatan Sinaboi Kabupaten Rokan Hilir”. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and analyzed. Test I (UH I) shows the increasing average score, from basic score 58,4 to 74,6, it increases 16,2 points (21,71%). And at the Test II (UH II) increase about 12,4 points (12,75%). So that, the average score is to be 87. Classically, total increasing from basic score to Test II (UH II) is 28,6 points (32,87%). The Classically Completing activity also increase about 36%, score percentage 20% at the Test I to be 64%. And at the Test II, percentage score is 84%, it increases 25%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 58,33%, and at the second is 75% (increase 16,67%). Fourth meeting, percentage of teacher activity is 79,17% (4,17%), and 91,67% (12,5%) at the fifth meeting. Student activity at the first meeting is 58,33%, and increase 12,5% at the second meeting to be 70,83%. Then, it is increasing to be 75,6% (4,77%) at the fourth meeting, and 87,5% (11,9%) at the fifth meeting. So, the conclusion is the Implementation Cooperative Learning Model type Two Stay Two Stray (TSTS) can improve Math studying result, Students of class IV SDN 005 Raja Bejamu Kecamatan Sanaboi. Keywords: Cooperative Learning Model type Two Stay Two Stray (TSTS), Math studying result, PTK.